Meaning of Life in Breast Cancer Survivors: A Qualitative Phenomenological Study - M. Imam Sya Roni; Abdul Haris Fitri Anto; Nova Lusiana (International Conference on Sustainable Health Promotion, 2025)
Breast cancer is one of the most common cancers worldwide and a major cause of mortality among women, significantly impacting their physical, psychological, and social well-being. Understanding how individuals find meaning in life is crucial to support their mental health and recovery process. This study aims to explore the lived experiences of breast cancer patients in constructing and understanding the meaning of life after diagnosis and treatment. Using a qualitative design with a phenomenological approach, three participants were selected through purposive sampling based on specific inclusion criteria. Data were collected through in-depth interviews and analysed using Interpretative Phenomenological Analysis (IPA) to identify emerging themes. The analysis revealed four main themes: self-acceptance, reflecting the process of accepting personal limitations and circumstances; life motivation, highlighting inner strength driven by family and spiritual values; support group, emphasizing the role of psychological and social support from communities and peers; and positive body image, showing how participants cope with changes in physical appearance and societal perceptions. These findings indicate that the meaning of life plays a central role in enhancing psychological resilience and improving quality of life among breast cancer patients. This study suggests that holistic interventions focusing on psychological, social, and spiritual aspects are essential to help individuals cope with the challenges of breast cancer and foster a sense of purpose and well-being.